Alpha 2‐Heremans‐Schmid glycoprotein gene polymorphism (rs4918) is associated with coronary artery calcification in incident peritoneal dialysis patients. Issue 1 (4th November 2022) - Dai, Shuqi; Chen, Yun; Shang, Da; Ge, Xiaolin; Yan, Huanqing; Hao, Chuanming; Zhu, Tongying
Abstract: Aim: Coronary artery calcification (CAC) is a common and severe complication in peritoneal dialysis (PD) patients, and it progresses in a majority of patients. Fetuin‐A, encoded by the alpha 2‐Heremans‐Schmid glycoprotein (AHSG) gene, is a serum calcification inhibitor. The study aimed to examine the role of AHSG gene polymorphism rs4918 in CAC and CAC progression of PD patients. Methods: Incident PD patients at Huashan Hospital Fudan University in China from August 2007 to July 2018 were recruited in this prospective study and followed up for 2 years. Patients underwent CAC measurements at recruitment and 2 years later. AHSG gene polymorphism rs4918 and serum fetuin‐A were determined at baseline. The demographic characteristics, clinical data, and laboratory data were collected during the follow‐up period. Binary logistic regression was performed to explore the association between rs4918 with CAC and CAC progression. Results: A total of 202 PD patients (112 men, 55.4%) were recruited, with a mean age of 54 ± 16 years. The multivariate logistic regression identified genotype GG as an independent risk factor that correlates to CAC (odds ratio [OR] = 2.153; 95% CI: 1.182–3.925; p = .012) and CAC progression (OR = 2.482; 95% CI: 1.422–4.330; p = .001). The serum fetuin‐A level was influenced by the rs4918 variants of AHSG, with a dose‐dependent effect depending on the number of the G allele. Conclusion: AHSG gene polymorphism rs4918 affects serum fetuin‐A levels and is significantly associated with both CAC and CAC progression in a cohort of patients receiving PD. Summary at a glance: AHSG gene polymorphism rs4918 affects serum fetuin‐A levels and is significantly associated with both coronary artery calcification (CAC) and CAC progression in a cohort of patients receiving peritoneal dialysis. The 767G allele increases the risk for CAC and CAC progression.